Knowledge, awareness and attitude on infant organ donation among medical students - Kataria, Raveena R.; Hullur, Himaad M.; Sayyed, Anjum; Pratinidhi, Shilpa A. (International Journal Of Community Medicine And Public Health, 2020)
Background: In India, without a viable donor nearly 5 lakh people die each year from organ failure. Infant organ donation, though a rare global phenomenon has been gaining momentum in transplantation and research. As future doctors who may counsel a potential donor family, medical students need an expanded knowledge and attitude to promote organ donation. Therefore, this study was conducted to determine the present knowledge of medical students, to identify areas lacking and to suggest measures to close these gaps. Methods: A uniquely designed questionnaire of open and closed ended questions related both to general and infant organ donation was distributed. Following this, an educational intervention was given and post intervention responses were calculated. Results: Overall improvement was seen after giving educational intervention about infant organ donation. Out of 65 participants, 23% (n=15) were aware about organ donation and organ donation day which improved to 92% (n=60). Only 8% (n=5) were initially familiar with paediatric organ donation, which increased to 94% (n=61). The support for paediatric organ donation increased from 65% (n=42) to 97% (n=63). Conclusions: Infant organ donation has unexplored potentials which can alter thousands of lives each year. As receptive learners and future physicians, medical students are most likely to understand these advancing medical sciences and its real life application. Our study demonstrates the substantial changes in student’s attitudes on foetal donation by a brief exposure through teaching sessions. Hence, lectures on progressive medical interventions such as infant organ donation should be encouraged in first year M.B.B.S itself.